Penggunaan Aplikasi Quizizz Paper Mode dalam Meningkatkan Motivasi Belajar Sejarah Kebudayaan Islam pada Siswa Kelas VIII Sekolah Menengah Pertama Al-Izzah Iibs Batu Malang - Arina Maemanah; Asma Karima Amir; Mutiara Erisqi Rama Gesta; Luthfiya Fathi Pusposari; Indah Aminatuz Zuhriyah (Al-Munawwarah : Jurnal Pendidikan Islam, 2026)
This research uses a qualitative approach with a descriptive research type. The research subjects consist of teachers and eighth-grade students at SMP Al-Izzah IIBS Batu Malang. Data collection techniques were carried out thru observation, interviews, and documentation. Data analysis uses an interactive model that includes data reduction, data presentation, and conclusion drawing. The validity of the data is tested thru source triangulation and technique triangulation. The research results show that the use of Quizizz Paper Mode is carried out thru the stages of planning, implementation, and evaluation of learning. In the planning stage, teachers prepare Quizizz accounts, create questions, and prepare barcodes used by students to answer questions. In the implementation stage, students participate in learning evaluations using barcodes scanned thru the Quizizz application. Supporting factors for the implementation of Quizizz Paper Mode include the availability of learning devices, internet access, network stability, and the practical use of barcodes that can be reused. The inhibiting factor found is the instability of the internet network, which sometimes disrupts the evaluation process. The use of Quizizz Paper Mode has a positive impact on students' learning motivation, as evidenced by the increased enthusiasm, activity, participation, and engagement of students in the learning process. In addition, the learning atmosphere becomes more interactive, enjoyable, and not monotonous. Thus, Quizizz Paper Mode can serve as an effective alternative technology-based evaluation media in enhancing the learning motivation of Islamic Religious Education among eighth-grade students at SMP Al-Izzah IIBS Batu Malang.